Yugoslavia and the unlikely success of the new international financial order - Ramšak, Jure (Filozofski fakultet, Odeljenje za istoriju, 2024)
The lack of a viable alternative to the existing monetary and financial systems that would integrate richer oil-producing countries in the G-77 coalition and the Non-Aligned Movement with their less fortunate fellow members proved to be the most persistent obstacle in the path to establishing South-South economic cooperation and thereby challenging the global trade patterns and financial architecture dominated by North Atlantic institutions. As a European country with sizeable industrial capacity but a chronic shortage of financial capital, Yugoslavia was vitally interested in the possibility of channelling enormous amounts of fresh petrodollars into the envisaged ’South Bank’, while remaining ambiguous about other alternative forms of financial cooperation among developing countries proposed from the beginning of the 1970s onwards. This paper is based on two sets of archival sources: 1) materials connected to Yugoslavia’s role as coordinator of the Working Group for NonAligned Countries Central Bank Cooperation, and 2) evidence of impediments to bilateral economic arrangements with Least Developed Countries caused by the absence of alternative exchange mechanisms, which provide grounds for a discussion on the inaptitude of Yugoslavia’s and, by extension, the G-77’s experiments in the context of 1980s neoliberalism